A Study And Analysis Of Watermarking Algorithms For Medical Images - Al-Qershi, Osamah Mohammed Abdo (2010)
Digital watermarking techniques hide digital data into digital images imperceptibly for different purposes and applications such as copyright protection, authentication, and data hiding. One of the objectives of health care management systems is to securely archive patients’ records. Moreover, these records may require very large media capacity to store, long time to transmit, and consequently incur higher cost. Classical encryption technology is an important tool that can be used to protect data transmitted over computer networks but it does not solve all digital data protection problems.